From bottom‐up to top‐down control of invertebrate herbivores in a retrogressive chronosequence. (23rd January 2023) - Kempel, Anne; Allan, Eric; Gossner, Martin M.; Jochum, Malte; Grace, James B.; Wardle, David A.
Abstract: In the long‐term absence of disturbance, ecosystems often enter a decline or retrogressive phase which leads to reductions in primary productivity, plant biomass, nutrient cycling and foliar quality. However, the consequences of ecosystem retrogression for higher trophic levels such as herbivores and predators, are less clear. Using a post‐fire forested island‐chronosequence across which retrogression occurs, we provide evidence that nutrient availability strongly controls invertebrate herbivore biomass when predators are few, but that there is a switch from bottom‐up to top‐down control when predators are common. This trophic flip in herbivore control probably arises because invertebrate predators respond to alternative energy channels from the adjacent aquatic matrix, which were independent of terrestrial plant biomass. Our results suggest that effects of nutrient limitation resulting from ecosystem retrogression on trophic cascades are modified by nutrient‐independent variation in predator abundance, and this calls for a more holistic approach to trophic ecology to better understand herbivore effects on plant communities. Abstract : In the long‐term absence of disturbance, ecosystems enter a decline phase with reductions in plant productivity and nutrients, yet the consequences for higher trophic levels are unclear. We show that nutrient availability strongly controls invertebrate herbivores when predators are few, but that there is a switch from bottom‐up to top‐down control when predators are common. This trophic flip probably arises because predators were not affected by cascading effects of plant productivity but also preyed on aquatic insects. Thus, classic theories of terrestrial community regulation can be incomplete when organisms forage across ecosystem boundaries.